Relationship among mathematics representation skills, mathematics anxiety, and problem-solving ability of 8th graders - Krisnanto, Dedy; Istiandaru, Afit (Universitas Ahmad Dahlan, 2021)
The purpose of this research was to determine whether there was a positive and significant relationship between mathematical representation skills and mathematical anxiety with the problem-solving abilities of eighth grade students of SMP N 2 Sedayu Bantul Yogyakarta. This research is a quantitative research involving 63 grade VIII students of SMP Negeri 2 Sedayu. The data collection method is carried out through data collection techniques in the form of questionnaires and tests. The questionnaire instrument was used to determine student learning anxiety while the test instrument was used to determine mathematical representation and problem-solving skills. Data analysis used multiple linear regression analysis method. The results showed that there was a positive and significant relationship between mathematical representation ability and mathematical anxiety with solving ability by using the F-test which resulted in F = 3.882 > 3.33 = F table with a significance level of 5%. While the correlation coefficient obtained is R = 0.3666. The regression equation is . The relative contribution of X1 is 57.88% and X2 is 42.11%. While the effective contribution of X1 is 12.24% and X2 is 8.904%.